Centre of excellence for pharmaceutical plant development : a case study of Jacobs Engineering Cork, Ireland. - Ivyne Rusli. (2008)
The report is a case study of attribution of the success of Jacobs Cork, an engineering and construction company that is in the supporting industry for the pharmaceutical sector in Ireland. A macro-environmental analysis is carried out to review the location of Ireland in terms of the influences to the engineering and construction industry.